2022
DOI: 10.1021/acs.energyfuels.2c01326
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous and Coexisting Hydrate Phases─Formation under Natural and Laboratory Conditions

Abstract: Natural gas hydrates are non-stoichiometric, crystalline solids composed of water and gas molecules. Dependent upon the source of the hydrate-forming gas, the structure and composition of the occurring natural gas hydrates may vary. In nature, the existence of structure I, structure II, and structure H hydrates containing predominantly methane but also other hydrocarbons, H2S, or CO2 could be verified. Interestingly, the number of reports on coexisting hydrate phases with different structures and compositions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 51 publications
(152 reference statements)
0
3
0
Order By: Relevance
“…While NGs are normally assumed to just form a single structure-II hydrate, various hydrate phases of different structures and guest gas composition may actually form, including C 2–4 stabilized s-II, mixed C 1 /C 2 rich s-II/s-I, and (nearly) pure C 1 (s-I and potential s-II) at higher subcoolings. , Therefore, at higher Δ T sub , in addition to the most stable s-II natural gas hydrate, other hydrate structures are likely to form, which could play a role in KHI performance, e.g., due to the variable ability of polymers to inhibit these.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While NGs are normally assumed to just form a single structure-II hydrate, various hydrate phases of different structures and guest gas composition may actually form, including C 2–4 stabilized s-II, mixed C 1 /C 2 rich s-II/s-I, and (nearly) pure C 1 (s-I and potential s-II) at higher subcoolings. , Therefore, at higher Δ T sub , in addition to the most stable s-II natural gas hydrate, other hydrate structures are likely to form, which could play a role in KHI performance, e.g., due to the variable ability of polymers to inhibit these.…”
Section: Resultsmentioning
confidence: 99%
“…Water moleculeseither in the form of ice, liquid, or vaporand suitably sized guest molecules (e.g., methane/C 1 , ethane/C 2 , propane/C 3 , and CO 2 ) can form clathrate hydrates under suitable PT (pressure–temperature) conditions, generally at lower temperatures and higher pressures . Depending on the size of guest molecules and PT conditions, different hydrate structures form, including cubic s-I, s-II, and hexagonal s-H. In multicomponent gas systems, various hydrate structures can coexist simultaneously depending on the gas composition and pressure/temperature conditions , and several hydrates with different compositions and structures can form at different subcooling temperatures…”
Section: Introductionmentioning
confidence: 99%
“…Zhu et al reported an account of the use of Raman spectroscopy to identify the structure and molar composition of hydrate and how in situ information on the kinetics of formation, decomposition, replacement, and molecular diffusion at the molecular level is obtained. Pan et al analyzed natural gas hydrate samples spatially resolved using Raman spectroscopy to identify whether these natural samples only show heterogeneity with regard to their cage occupancy and composition or whether they already show coexistent phases. In a mini review, Uchida et al summarized the technologies for promoting the nucleation process in gas hydrate formation in addition to an account of recent studies on ultrafine bubbles to reduce induction time.…”
Section: Fundamentalsmentioning
confidence: 99%